Reservoir heterogeneity and quality of Khuff carbonates in outcrops of central Saudi Arabia. (January 2018) - Adam, Ammar; Swennen, Rudy; Abdulghani, Waleed; Abdlmutalib, Ammar; Hariri, Mustafa; Abdulraheem, Abdulazeez
Abstract: The Khuff carbonates host several main gas reservoirs in the Middle East. These reservoirs are known for their heterogeneity, both of sub-seismic scale and beyond the interwell spacing. To get a better insight in these reservoirs, the heterogeneity of the Upper Khartam Member, placed in a high-frequency sequence stratigraphic framework, was studied with a lateral resolution between logged sections of 5 m. The sedimentology and sequence stratigraphy of four outcrop localities were studied, and approximately 600 samples were collected for petrographic, porosity and permeability analyses. Seventeen lithofacies types were recognised and six major diagenetic processes could be differentiated in the studied outcrops. Dissolution is likely the result of intensive circulation of meteoric water undersaturated with respect to calcite. Significantly, cementation has blocked most of the original intergranular porosity. Pore lining detrital clay severely impacted reservoir permeability and complicated the pore geometry. Dolomitization is associated with the upper Khuff–Sudair boundary, and is likely the result of influx of water highly saturated with Mg +2 that developed during the deposition of the Sudair evaporites. Finally, stylolites are to a major extend controlled by lithofacies and geobody configuration. Ten porosity types could be namely: intergranular, intragranular, shelter, dissolution-enlarged, moldic, vuggy, micro-porosity, and porosity in relation to dolomite–dedolomite, dolomite-leaching, and fracture development. Overall intertidal creeks are characterized by a complex and heterogeneous pore geometry if compared to the intertidal channels, and this can be attributed to the geobody architecture, with intertidal creeks being composed of dense and small tidal bodies (1 m in length and 20 cm in thickness), while intertidal channels are composed of thick amalgamations of intertidal channels (5 m by 50 cm). Most critically, the horizontal reservoir quality was influenced differentially by diagenesis, which resulted in a lateral segmentation of single bodies into different, hydraulic units. The differential mold-filling calcite cements have significantly reduced porosity and permeability. Generally, mineral content has little impact on the reservoir quality, although clay minerals played a central role in lining the pore space and affecting permeability. Finally, horizontal reservoir heterogeneity seems to have been controlled by fractures and stylolites which respectively acted as conduits to and barriers for vertical fluid flow and, hence, controlled the differential cementation and dissolution processes. Highlights: Diagenetic processes have impacted the ultimate reservoir quality. Clay minerals have played a central role in affecting reservoir quality. Dissolution and cementation have differentially impacted the intra-reservoir quality. Dissolution and cementation have been controlled by fractures and stylolites.